1998
DOI: 10.1111/j.1528-1157.1998.tb01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Neuropsychological Data to the Prediction of Temporal Lobe Epilepsy Surgery Outcome

Abstract: Summary: Purpose:We empirically examined the contribution of' neuropsychological data to the prediction of postoperative seizure control relative to base rate information in an existing series of patients undergoing anterior temporal lobectomy (ATL).Methods: A discriminant function predicting surgery outcome (seizure-free vs. non-seizure-free) was computed separately for samples of patients with left (n = 79) and right (n = 62) temporal lobectomy (LATL, RATL). Predictor variables included 14 measures tapping f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The potential value of the WMS-IV measures to predict seizure freedom for patients with localization-related epilepsies, particularly among those individuals who are MRI negative for abnormalities, also should be investigated [10,[34][35][36]. Additionally, WMS-IV studies with concurrent functional imaging data among both healthy samples and samples with TLE could explore the neural substrates involved in performance on the WMS-IV memory subtests.…”
Section: Discussionmentioning
confidence: 95%
“…The potential value of the WMS-IV measures to predict seizure freedom for patients with localization-related epilepsies, particularly among those individuals who are MRI negative for abnormalities, also should be investigated [10,[34][35][36]. Additionally, WMS-IV studies with concurrent functional imaging data among both healthy samples and samples with TLE could explore the neural substrates involved in performance on the WMS-IV memory subtests.…”
Section: Discussionmentioning
confidence: 95%
“…(b) Predicting seizure freedom. Although limited to select cases, emerging studies have shown neuropsychological data can add unique variance in predicting likelihood a patient will be seizure-free after surgical treatment (e.g., Helmstaedter and Kockelmann 2006;Keary et al 2007;Potter et al 2009;Sawrie et al 1998;Seidenberg et al 1998). Often the additive predictive value is demonstrated for individuals with normal neuroimaging (i.e., nonlesional) or incongruent ictal and inter-ictal EEG findings, and generally have not included multiple non-invasive studies in addition to neuropsychological data (e.g., MEG/MSI, fMRI, PET, SISCOM studies).…”
Section: Hallucinationsmentioning
confidence: 99%
“…Often the additive predictive value is demonstrated for individuals with normal neuroimaging (i.e., nonlesional) or incongruent ictal and inter-ictal EEG findings, and generally have not included multiple non-invasive studies in addition to neuropsychological data (e.g., MEG/MSI, fMRI, PET, SISCOM studies). A recent study combining multiple predictors did not find that neuropsychological data added unique variance (Bell et al 2009 (Akunama et al 2003;Helmstaeder 2004;Hennessy et al 2001;Keary et al 2007;Potter et al 2009;Rausch 2006;Sawrie et al 1998). Alternatively, neuropsychological data have clear utility to evaluate the functional adequacy of mesial temporal lobes and other cerebral areas (e.g., Baxendale and Thompson 2010;Chelune 1995;Seidenberg et al 1998;Stroup et al 2003).…”
Section: Hallucinationsmentioning
confidence: 99%
See 2 more Smart Citations